A particle starting from rest moves in a straight line with acceleration proportional to x^2, (where x i displacement). The gain of kinetic energy for any displacement is proportional to :
1) x^3
2)x^1/2
3)x^2/3
4)x^2
Answers
Answered by
78
Acceleration is proportional to x²
e.g., a = Kx²
Here , a is the acceleration and K is proportionality constant
vdv/dx = Kx²
⇒∫vdv = K∫x²dx
⇒ v²/2 = Kx³/3
⇒v² = 2Kx²/3 ----------(1)
we know,
kinetic energy = 1/2 mv²
= 1/2 m (2Kx³/3) = mKx³/3 [ from equation (1)
Here it is clear that kinetic energy is directly proportional to x³.
So, correct option ( 1 )
e.g., a = Kx²
Here , a is the acceleration and K is proportionality constant
vdv/dx = Kx²
⇒∫vdv = K∫x²dx
⇒ v²/2 = Kx³/3
⇒v² = 2Kx²/3 ----------(1)
we know,
kinetic energy = 1/2 mv²
= 1/2 m (2Kx³/3) = mKx³/3 [ from equation (1)
Here it is clear that kinetic energy is directly proportional to x³.
So, correct option ( 1 )
Answered by
9
》》Here , it is said that "Acceleration (a) is proportional to Displacement (
).
So , by removing proportionality
, where 'k' is a proportionality constant
We can write
....( you can check by seeing unit using dimensional formula)
![\frac{v×dv}{dx} = kx^{2} \frac{v×dv}{dx} = kx^{2}](https://tex.z-dn.net/?f=%5Cfrac%7Bv%C3%97dv%7D%7Bdx%7D+%3D+kx%5E%7B2%7D)
Multiply both side by dx
![v×dv = kx^{2} × dx v×dv = kx^{2} × dx](https://tex.z-dn.net/?f=v%C3%97dv+%3D+kx%5E%7B2%7D+%C3%97+dx)
Integrating both sides
![∫v×dv = ∫kx^{2} × dx ∫v×dv = ∫kx^{2} × dx](https://tex.z-dn.net/?f=%E2%88%ABv%C3%97dv+%3D+%E2%88%ABkx%5E%7B2%7D+%C3%97+dx)
........ Since ∫x×dx =![\frac{x^(n+1) }{n+1} \frac{x^(n+1) }{n+1}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E%28n%2B1%29+%7D%7Bn%2B1%7D)
![v^{2 }= \frac{2x^{3}}{3} v^{2 }= \frac{2x^{3}}{3}](https://tex.z-dn.net/?f=v%5E%7B2+%7D%3D+%5Cfrac%7B2x%5E%7B3%7D%7D%7B3%7D)
As we got
we can substitute its value in Equation of Kinetic energy.
Kinetic Energy =![\frac{1}{2} mv^{2} \frac{1}{2} mv^{2}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D+mv%5E%7B2%7D)
Substituting value of![v^{2} v^{2}](https://tex.z-dn.net/?f=v%5E%7B2%7D)
Kinetic Energy =![\frac{1}{2} m× \frac{2x^{3}}{3} \frac{1}{2} m× \frac{2x^{3}}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D+m%C3%97+%5Cfrac%7B2x%5E%7B3%7D%7D%7B3%7D)
Kinetic Energy =![\frac{mx^{3}}{3} \frac{mx^{3}}{3}](https://tex.z-dn.net/?f=%5Cfrac%7Bmx%5E%7B3%7D%7D%7B3%7D)
Take![\frac{m}{3} = K \frac{m}{3} = K](https://tex.z-dn.net/?f=%5Cfrac%7Bm%7D%7B3%7D+%3D+K+)
Therefore,
Kinetic Energy =![Kx^{3} Kx^{3}](https://tex.z-dn.net/?f=Kx%5E%7B3%7D)
So , Kinetic energy is directly proportional to![x^{3} x^{3}](https://tex.z-dn.net/?f=x%5E%7B3%7D)
I.e your answer OPTION [1]
So , by removing proportionality
We can write
Multiply both side by dx
Integrating both sides
As we got
Kinetic Energy =
Substituting value of
Kinetic Energy =
Kinetic Energy =
Take
Therefore,
Kinetic Energy =
So , Kinetic energy is directly proportional to
I.e your answer OPTION [1]
Similar questions